Surface crack analysis of the steering shaft gear after carburizing and quenching. (November 2022) - Zhang, Yishuai; Sun, Hongxing; Liu, Baixuan; Liu, Dan; Xu, Wenbo; Liu, Shijun; Zhang, Chao; Wang, Jinbao; Liu, Hua
Highlights: Linear surface crack can be formed on the surface of the round steel because of non-metallic inclusions during the rolling process. The shape of the surface crack can be changed during gear forging process with material flow. Open cracks can provide diffusion channels for carbon atom diffusion during carburizing and quenching. The shape of the surface crack changed in forging can be numerically simulated and reproduced with the help of point tracking technology in finite element analysis. Abstract: The phenomenon of surface cracks in steering shaft gear after carburizing and quenching was analyzed by combining experimental research, theoretical analysis, and numerical simulation. The chemical composition, crack morphology, non-metallic inclusions, microstructure, microhardness, and forging process were analyzed and studied by means of directly reading spectrometer, metallographic microscope, scanning electron microscope, energy dispersive spectrometer, and micro hardness tester. The evolution process of surface crack morphology was numerically simulated and reproduced with the help of Deform 3D point tracking technology. The results show that linear surface cracks are formed on the surface of the round steel because of Alumina-type non-metallic inclusions, which destroy the continuity of the steel matrix during the rolling process. Surface cracks become arc-shaped due to the regular plastic flow direction of the material and propagate in the depth direction during the forging process. Crack provide a channel for the diffusion of C atoms during carburizing and quenching process, therefore carburized layer with gradient distribution is formed on both sides of the crack. The carburized layer reacts with oxygen during quenching and subsequent tempering, resulting in a certain degree of oxidation on both sides of the crack and the crack tail. Therefore, the surface cracks found in the steering shaft gear after carburizing and quenching are originated from the rolling cracks formed by non-metallic inclusions of steel. The rolling cracks have undergone further evolution in the subsequent forging and carburizing quenching process.